Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the capital inflows to Indonesia since the global financial crisis. Capital inflows to Indonesia have increased since the crisis. Their average volume increased from 3.25 percent of GDP in 2005-09 to 4.50 percent of GDP in the first quarter of 2010 to the third quarter of 2016. From the global perspective, driven by the liquidity released from the systemic economies' unconventional monetary policies, a global search for yields has led to large capital inflows to emerging and developing economies (EMDEs), especially portfolio inflows. Although many EMDEs experienced a steady decline in capital inflows during 2013-16, capital inflows to Indonesia increased and reached a peak in late 2014, and then started to decline but remained at relatively high levels from the first quarter of 2015 to the third quarter of 2016.